Pengembangan Media Papan Pecahan Semangka pada Materi Membandingkan dan Mengurutkan Nilai Pecahan di Kelas IV SDN Sutorejo I/ 240 Surabaya - Devi Amelia; Moh. Edi Nurtamam (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Learning fraction concepts remains a challenge for many elementary school students because the material is abstract and requires concrete representations to facilitate conceptual understanding. Therefore, this study develops the Watermelon Fraction Board Media as an innovative learning medium to support mathematics instruction and evaluates its feasibility in terms of validity, effectiveness, and attractiveness. This study employs the Research and Development (R&D) method, referring to the ADDIE development model. It aims to describe the development procedure and the feasibility of the Papan Pecahan Semangka Media, evaluated in terms of validity, effectiveness, and attractiveness for the Mathematics subject, Chapter 2 Topic A, in grade IVA of SDN Sutorejo I/240 Surabaya. The product's feasibility is assessed based on three aspects: validity, effectiveness, and attractiveness. The validation results indicate that the media achieved a percentage of 92% from the media expert (highly valid), 86% from the learning device design expert (highly valid), and 82% from the material expert (valid). Regarding effectiveness, the learning test results from the large-group trial showed an average student score of 87.77 with a classical completeness percentage of 95.45%, while the observation results of student and teacher activities obtained percentages of 90.38% and 95.8%, respectively, all categorized as highly effective. In terms of attractiveness, the teacher response questionnaire obtained a percentage of 100%, and the student response questionnaire reached 91.51%, both categorized as attractive. Based on these overall results, the Watermelon Fraction Board Media is declared feasible for use in mathematics learning activities in grade IV of elementary school.